Peran Pengajian Bulanan dalam Membentuk Sikap Beragama Siswa di SMAS Budi Agung Medan - Azaman Andra; Mahariah Mahariah; Makmur Syukri (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study focuses on the importance of the role of monthly religious studies in shaping students’ religious attitudes at SMAS Budi Agung Medan, considering that religious studies are one of the effective means to teach religious values, strengthen faith, and shape students’ character and morals in everyday life. The method used is a qualitative method with a descriptive approach. Data collection was carried out through documentation, observation and interviews. The subjects of the study were the principal, vice principal for student affairs, Islamic Religious Education teachers, and students. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. The results of the study showed that (1) Monthly religious studies activities at SMAS Budi Agung Medan are carried out once a month on the first week starting at 08.00 to 11.00 WIB at the Al-Huda Marelan Mosque. The three activities carried out in this monthly religious study are the opening, core and closing. (2) The materials discussed include faith, jurisprudence, morals, as well as the Qur’an and Hadith of the Prophet. (3) The role of monthly religious studies in forming the religious attitudes of SMAS Budi Agung Medan students includes spiritual, moral, social and educational roles. (4) The monthly religious study program held at SMAS Budi Agung Medan is considered to have a positive impact on SMAS Budi Agung Medan students, because the religious studies are able to gradually improve the students’ religious attitudes.